Simulation study of a major bridge rehabilitation project in Sri Lanka - Cheah, Francis Kok Seng. (2009)
The objective of this thesis is to study, evaluate and attempt to quantify the effects of the site conditions, resources output, availability and reliability on the productivity rates of a major bridge rehabilitation project. The project that was chosen was the rehabilitation of a major bridge in Sri Lanka called the New Kelani Bridge. In particular the methodology was used to conduct a post-mortem analysis of a sub-system of the whole project that resulted in a delay in the project.